Faktor-Faktor yang Memengaruhi Pekerja Anak di Provinsi Nusa Tenggara Timur Tahun 2021 - Alwi, Rahmi Maulina; Sirait, Timbang (Politeknik Statistika STIS, 2023)
Child labor is a global issue contained in SDG's goal 8.7 which envisions the end of child labor in all its forms by 2025. In 2021 it is known that the province of NTT has a high number of child workers and ranks eighth out of 34 provinces in the world. Indonesia, and is above the national average. Much research has been done on child labor, but not much has considered the imbalance between success and failure in this child labor phenomenon. This research was conducted to determine the characteristics of child labor in the province of NTT in 2021 and the factors that influence it by using the firth logistic regression method which takes into account estimation bias in unbalanced data conditions. The research was conducted using data from the national socio-economic survey core module for March 2021. From the research it was found that the factors that influence child labor are the child's education level, child's age, child's gender, and marital status of the head of household.